Pneumonia - Muthia Zahra; Puspa Rosfadilla (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Pneumonia is an infection or acute inflammation of the lung parenchyma characterized by infiltrates in the lungs, accompanied by complaints of coughing and shortness of breath. Basic Health Research data in 2018 showed that pneumonia patients increased with age. The pneumonia rate in Indonesia reached 1,017,290 people, Aceh Province amounted to 20,244 people. Patient Mr. Mr. H, 68 years old, came to the emergency room of Cut Meutia Hospital with complaints of shortness of breath felt since 3 days SMRS and worsened one day before being brought to the emergency room. The patient also complained of an occasional cough that had been felt for one month, and had worsened since one week SMRS, coughing sometimes accompanied by yellowish white sputum. On auscultatory examination of the lungs, additional breath sounds were obtained, namely ronkhi in both lung fields. The treatment given was antibiotics and other symptomatic therapy.